Risk factors and preventive measures for breast cancer - Winkler, Marie-Christin; Hetjens, Svetlana (Journal of Clinical Medicine, 2024)
Background: Breast cancer is the most common cancer in women in many countries. Breast cancer is a multifactorial disease. This study investigates the possible influencing factors and preventive measures for breast cancer. Methods: The data for this study were obtained from WHO databases. First, age standardization was performed, followed by a correlation analysis. Relationships between the mortality rates of breast cancer and the possible influencing factors were analyzed. The significant results from the correlation analysis were analyzed using a stepwise regression analysis. In order to find out whether the application of a uniform screening program can reduce breast cancer mortality, the countries were divided into groups according to the time of initiation of the screening program, and breast cancer mortality was compared. Results: The correlation analysis showed a significant relationship with breast cancer mortality for 15 of 30 potential influencing factors. A stepwise multivariate regression analysis was performed with these 15 factors, which revealed 13 relevant factors. Two factors were more relevant: the number of radiotherapy units per 100,000 inhabitants and the proportion of the population (over 50 years of age) with a social network. These were followed by the proportion of general practitioners and obstetricians, as well as healthcare expenses. Breast cancer mortality differed between the countries that introduced the screening program in the 1990s and those that did so in the 2020s. Conclusions: A country’s healthcare system influences breast cancer mortality through prevention, diagnosis. and treatment. Regular screening, counseling for socially disadvantaged women, and prompt treatment are important factors. In the future, prevention measures should also aim to strengthen the social environment. The prescription of social activities should be used as preventive care.
Gesehen am 10.03.2025